2019
DOI: 10.31236/osf.io/xaum3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physical activity, mental and personal wellbeing, social isolation, and perceptions of academic attainment and employability in university students: Pooled analysis of the Scottish and British Active Students Surveys

Abstract: Background: Achieving sufficient physical activity (PA) promotes health and wellbeing. For students, university represents a transitional period including increased independence over lifestyle behaviors, in addition to new stressors and barriers to engaging in PA. It is therefore important to monitor PA trends in students to gain a greater understanding about the role it might play in physical and mental wellbeing, as well as other factors such as attainment, and employability. Methods: Cross-sectional surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Perceived increased physical activity since the start of the pandemic, however, was not found to be related to perceived increased feelings of loneliness since the start of the pandemic-related restrictions as the only significant correlate was the general (static) loneliness. Previous studies such as a United Kingdom study found that active students were less likely to experience loneliness compared to inactive students (Budzynski-Seymour et al, 2019). The same result was also found in the general population on a meta-analytical level (Pels and Kleinert, 2016).…”
Section: Discussionsupporting
confidence: 73%
“…Perceived increased physical activity since the start of the pandemic, however, was not found to be related to perceived increased feelings of loneliness since the start of the pandemic-related restrictions as the only significant correlate was the general (static) loneliness. Previous studies such as a United Kingdom study found that active students were less likely to experience loneliness compared to inactive students (Budzynski-Seymour et al, 2019). The same result was also found in the general population on a meta-analytical level (Pels and Kleinert, 2016).…”
Section: Discussionsupporting
confidence: 73%